The Effectiveness of a University Mentoring Project in Peri-rural Australia - Drummond, Aaron; Halsey, John; Lawson, Mike; van Breda, Maria (Australian and International Journal of Rural Education, 2012)
The Bradley report (2008) recommended that there be an increase in the percentage of young Australian‟s completing a university degree, with a subsequent target set by the Australian Federal Government to 40% of 25-34 years olds holding a first degree by 2025. As students who transition to university following completion of high school in medium-high social economic status urban areas is already often high (>90% in some cases), one obvious target for any increase is in peri-rural (distance from metropolitan areas approaching 80km) and rural areas (distance from metropolitan areas >80km in accordance with Jones, 2000). In 2010, a youth mentoring project was initiated targeting year nine students in a peri-rural area school. The project sought to increase the interest of these students in attending university post high school graduation. The present paper presents the preliminary data for 18 students in the first round of the mentoring project. Participants were asked to rate their estimated percentage chance they would attend university following school completion, as well as to estimate how much contact they had with university mentors across several questionnaire items. Mentor contact items were averaged to give an overall measure of mentor contact. Measures of mentor contact were significantly correlated with participants estimates of the percentage chance they would attend university, r = .59, p < .01, r2 = .35 as well as their self identification with university students as an „in-group‟, r = .75, p < .01, r2 = .56. Further, percentage chance participants would attend university was significantly correlated with students‟ self identification with university students as an „in-group‟, r = .60, p < .01, r2 = .36. One potential pathway for this effect was that contact with mentors increased students „in-group‟ identification with university students, which in turn increased their estimated chance of going to university. Concordant with this prediction, regression analysis indicated that the unique effect of mentor contact was reduced to non-significance when the effect of in-group identification was controlled for, R2 change = .05. Similar findings were observed for participants‟ ratings of how much they liked university. The present results imply that if rural students can make meaningful contact among university students through pilot programs such as the present one, then they are more likely to consider university as a viable option for themselves at high school completion. Follow up data will be able to confirm whether these student perceptions link with post graduation behaviour. Results are discussed with regard to their implications about higher education pathways in the university and vocational education sectors in rural Australia.